Modelling the impact of the COVID-19 pandemic on cancer stage migration and excess mortality in Ireland - Mengyang Zhang; Paula Tierney; Aline Brennan; Deirdre Murray; Maeve Mullooly; Kathleen Bennett (Preventive Medicine Reports, 2025)
Background: Cancer treatment services were interrupted during the pandemic, which potentially increased the time to treatment initiation (TTI). This study aimed to model the impact of a hypothetical three- and six-month delay in TTI on stage of breast cancer and non-small cell lung cancer (NSCLC) in Ireland. Methods: The distribution of cancer stage at diagnosis, net survival at one to five years post diagnosis, and projected cancer incidence for 2020 were obtained for breast cancer and NSCLC, from the National Cancer Registry Ireland. The primary outcome, the probability of an upward stage-shift from stage I to II and stage II to III, is presented with 95 % CIs. Results: For breast cancer, the stage-shift probability after a hypothetical three-month and six-month delay was 0.13 (0.11, 0.15) and 0.25 (0.21, 0.27) in stage I and 0.09 (0.08, 0.11) and 0.17 (0.14, 0.21) in stage II. For NSCLC, the stage-shift probability after three-month and six-month delays was 0.51 (0.49, 0.53) and 0.76 (0.74, 0.78) in stage I and 0.27 (0.24, 0.30) and 0.47 (0.43, 0.51) in stage II. Conclusions: The study provides potential evidence for an upward stage migration in those with breast cancer and NSCLC due to the pandemic. It is important to determine the longer-term impacts so that strategies are developed to mitigate adverse effects and improve health system preparedness for future unprecedented events.